Pendekatan Deep Learning untuk Pembelajaran IPA yang Bermakna di Sekolah Dasar - Nabila, Siti Maulidiya; Septiani, Melinda; Fitriani, Fitriani; Asrin, Asrin (Magister Pendidikan Dasar FKIP Universitas Mataram, 2025)
This research aims to examine the integration of the deep learning approach and the implementation of the Merdeka Curriculum in science learning at the elementary school level. The deep learning approach emphasizes the principles of mindful, meaningful, and joyful learning, which are in line with the philosophical direction of the Merdeka Curriculum which emphasizes differentiated, flexible, and contextual learning. This research uses a literature study method by analyzing 24 relevant national scientific articles. The study results show that science learning can be optimized through strategies such as project-based learning, inquiry-based learning, and the application of learning differentiation, supported by digital media and authentic assessment. The main obstacles found include teachers' low digital literacy, limited resources, and challenges in deep learning planning. Proposed solutions include practice-based training, strengthening teacher learning communities, developing contextualized teaching modules, and collaboration between schools and universities. With policy support and continuous assistance, the application of deep learning in science learning has the potential to encourage the strengthening of science literacy, student character, and 21st century competencies more optimally.